Low-cost acidic cut-off oxygen evolution catalyst and synthesis method thereof

By incorporating SnO2 and nickel into RuO2, the Sn0.9-xRu0.1Ni0.1O2 catalyst is formed, and the problems of high cost and insufficient activity of iridium-based catalysts are solved, and the efficient oxygen precipitation reaction under acidic conditions is achieved, reducing the catalyst Cost and improve stability and activity, suitable for water decomposition applications of green energy.

CN119287441APending Publication Date: 2025-01-10YANGTZE DELTA REGION INST OF UNIV OF ELECTRONICS SCI & TECH OF CHINE (HUZHOU)
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411401981.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-09
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

In the prior art, iridium-based catalysts are difficult to commercialize due to high cost, and the activity and stability of electrocatalytic water decomposition of hydrogen under acidic conditions are insufficient, making it difficult to replace IrO2 catalysts, resulting in the development of low-cost and highly active oxygen precipitation reactions. (OER) electrocatalysts are a challenge.

Method used

By doping active but unstable ruthenium (Ru) with relatively inert but stable tin (Sn), and introducing nickel (Ni), SnO2 is incorporated into the RuO2 matrix to form a Sn0.9-xRu0.1Ni0.1O2 catalyst, Reduce the amount of ruthenium, improve the stability and activity of the catalyst, and utilize the same rutile structure and high conductivity to improve electrochemical performance.

Benefits of technology

Achieve efficient oxygen precipitation reaction under acidic conditions, reduces the cost of the catalyst, improves electrochemical stability and activity, exhibits higher current density and lower OER overpotential, suitable for water decomposition applications of green energy .

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119287441A_ABST
    Figure CN119287441A_ABST
Patent Text Reader

Abstract

The invention discloses a synthesis method of a low-cost acidic cut-off oxygen evolution catalyst, which comprises the following steps: (1) dissolving SnCl4. 5H2O, RuCl3 and NiCl2 in ethanol to prepare a mixed solution; (2) adding HCl into the mixed solution, and performing ultrasonic treatment to form a uniform solution; (3) transferring the uniform solution into a water bath, and keeping the reaction for several hours at a certain temperature until a solid solution is formed; (4) completely drying the solid solution in a drying oven to prepare a precursor; (5) carrying out annealing treatment on the precursor in air in a tubular furnace, and collecting a black product; and (6) cleaning the black product with water, and then cleaning with ethanol to remove impurities, thereby obtaining the low-cost acidic cut-off oxygen evolution catalyst. The catalyst disclosed by the invention is simple in preparation method, mild in operation condition and relatively high in repeatability, and shows excellent catalytic activity in an acid environment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of catalyst preparation, and particularly relates to a low-cost acidic cut-off oxygen evolution catalyst and a synthesis method thereof. Background Art

[0002] As a representative energy carrier with high energy density and sustainability, the demand for hydrogen is growing day by day. Electrocatalytic water decomposition into hydrogen and oxygen molecules is regarded as one of the most promising green technologies that can alleviate or even solve the increasingly serious environmental and energy crises, and has therefore attracted widespread attention. Materials based on ruthenium (Ru) and iridium (Ir) remain the most advanced catalysts with excellent activity under acidic conditions. Since Ru-based materials have better activity than Ir-based materials, the development of Ru-based catalysts is of great significance for improving polymer electrolyte membrane (PEM) electrolyzers. PEM electrolyzers are the most promising electrolysis technology that can operate under corrosive acidic conditions and overcome the defects of alkaline media. The development of active, acid-stable and cost-effective oxygen evolution reaction (OER) electrocatalysts is the main challenge for direct hydrogen production via water electrolysis. IrO2 is the most famous catalyst in acidic media, known for its good stability, but its cost is too high to be commercialized. Therefore, to overcome this economic limitation, alternative electrocatalysts must be developed. In recent years, ruthenium-based catalysts have attracted widespread attention in OER due to their better activity and relatively lower cost compared with iridium-based catalysts.

[0003] As the demand for intermittent renewable energy generation increases, energy storage becomes increasingly important. Hydrogen production through water electrolysis offers a promising solution to this challenge. Among existing technologies, proton exchange membrane water electrolyzer (PEMWE) is an ideal choice for clean energy hydrogen production due to its high current density, excellent energy conversion efficiency, low gas permeability, compact size, and fast dynamic response. However, the harsh corrosive environment and high anode overpotential in PEMWE require electrode materials with higher activity and durability. Summary of the invention

[0004] In view of the problems existing in the background technology, the purpose of the present invention is to present an acidic OER catalyst Sn 0.9- x Ru 0.1 Ni 0.102(x=0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8) design strategy, that is, by doping the active but unstable element ruthenium (Ru) with the relatively inert but stable element tin (Sn), and improving its activity by co-doping with nickel (Ni). A common stability enhancement method is to obtain a more stable OER electrocatalyst by doping the stabilizing oxide SnO2 into the active oxide (such as RuO2), minimize the amount of ruthenium, and thus reduce the cost of precious metals. The incorporation of SnO2 into the RuO2 matrix not only improves the utilization of the ruthenium species, but also improves the electrochemical stability. In addition, SnO2 has the same rutile structure as RuO2, exhibits higher conductivity and lower OER overpotential, and their lattice parameters are also very similar (SnO2: RuO2: ). However, when tin is doped with ruthenium, the resulting mixture exhibits higher current density than the single oxides, and the solid solution shows greater stability. The effectiveness of this strategy is limited by the low solubility of these dopants in the rutile oxide matrix.

[0005] In order to achieve the above technical objectives, the present invention adopts the following technical solutions:

[0006] A method for synthesizing a low-cost acidic cut-off oxygen evolution catalyst comprises the following steps:

[0007] (1) Dissolving SnCl4·5H2O, RuCl3 and NiCl2 in ethanol to prepare a mixed solution;

[0008] (2) adding HCl to the mixed solution obtained in step (1) and forming a homogeneous solution by ultrasonic treatment;

[0009] (3) transferring the homogeneous solution obtained in step (2) into a water bath and maintaining the reaction at a certain temperature for several hours until a solid solution is formed;

[0010] (4) completely drying the solid solution obtained in step (3) in an oven to obtain a precursor;

[0011] (5) annealing the precursor obtained in step (4) in air in a tube furnace and collecting a black product;

[0012] (6) Washing the black product collected in step (5) with water, and then washing with ethanol to remove impurities, thereby obtaining a low-cost acidic cut-off oxygen evolution catalyst.

[0013] Preferably, the SnCl4·5H2O in step (1) is 0.175 g, the RuCl3 is 0.104 g, and the NiCl2 is 0.0237 g.

[0014] Preferably, the amount of ethanol in step (1) is 10 ml.

[0015] Preferably, in step (2), the amount of HCl is 0.5 ml.

[0016] Preferably, the ultrasonic treatment time in step (2) is 1 hour.

[0017] Preferably, in step (3), the reaction is maintained at 60° C. for 12 hours until a solid solution is formed.

[0018] Preferably, the temperature of the oven in step (4) is 60°C.

[0019] Preferably, the annealing conditions in step (5) are: annealing at 450° C. for 2 hours.

[0020] Preferably, in step (6), the black product is washed three times with water and then washed once with ethanol to remove impurities, thereby obtaining a low-cost acidic cut-off oxygen evolution catalyst.

[0021] The present invention relates to a novel Sn 0.9-x Ru x Ni 0.1 The synthesis method of O2 (x = 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8) nanostructures is specially designed to enhance the oxygen evolution reaction (OER) activity in acidic environments for water splitting applications. The catalyst exhibits high performance as an OER catalyst and can achieve complete electrocatalytic water splitting. The advantages are as follows:

[0022] (1) This OER catalyst has application prospects in water decomposition under acidic conditions, bringing significant progress to green energy applications.

[0023] (2) The key advantage of this study is the synthesis of a new OER catalyst with excellent catalytic activity.

[0024] (3) XRD spectrum confirmed the successful synthesis of Sn 0.9-x Ru 0.1 Ni 0.1 O2(x=0.1,0.2,0.3,0.4,0.5,0.6,0.7,0.8), such as Figure 1 In addition, the catalyst is conducive to directional electron transport, further improving its performance.

[0025] (4) The preparation method is simple, the operating conditions are mild, it has strong reproducibility, and it exhibits excellent catalytic activity in an acidic environment.

[0026] (5) Sn 0.9-x Ru 0.1 Ni 0.1O2 (x = 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8) nanoparticles will play an important role in the green energy production of carbon-free energy.

[0027] (6) OER catalyst Sn of the present invention 0.9-x Ru x Ni 0.1 O2 was synthesized by a simple solid solution method and calcined at 450 °C for 2 h, successfully achieving high-performance application for water splitting under acidic conditions, providing a significant advancement for green energy applications.

[0028] (7) Low-cost materials: The catalyst of the present invention will maintain a favorable cost competitive advantage because the price of Ru is significantly lower than that of iridium (Ir). BRIEF DESCRIPTION OF THE DRAWINGS

[0029] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the following briefly introduces the drawings required for use in the embodiments of the present invention. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.

[0030] Figure 1 :Sn 0.9-x Ru x Ni 0.1 Graphic illustration of O2.

[0031] Figure 2 : XRD patterns of the samples.

[0032] Figure 3 :(a) Sn 0.5 Ru 0.4 Ni 0.1 SEM images of O2, (b) Sn 0.5 Ru 0.4 Ni 0.1 EDS images of O2, (c) Sn 0.5 Ru 0.4 Ni 0.1 Elemental distribution diagram of O2.

[0033] Figure 4 : Diagram of the electrode preparation process.

[0034] Figure 5 :Sn 0.9-x Ru x Ni 0.1 O2 and Sn 0.5 Ru 0.4 Electrocatalytic OER performance of O2 in 0.5M H2SO4 electrolyte.

[0035] Figure 6 :Sn 0.4 Ru 0.5 Ni 0.1 O2 and Sn 0.4 Ru 0.6 Tafel slope plot of O2.

[0036] Figure 7 :Sn 0.4 Ru 0.5 Ni 0.1 Stability diagram of O2. DETAILED DESCRIPTION

[0037] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0038] 1. Experimental part

[0039] 1.1. Materials

[0040] Ruthenium trichloride (RuCl3), tin chloride hydrate (SnCl4·5H2O), and nickel chloride (NiCl2) were purchased from China Pharmaceutical Group. Sulfuric acid (H2SO4) and hydrochloric acid (HCl) were purchased from Sinopharm Chemical Reagent Co., Ltd. 5wt% Nafion solution and ethanol (99.9%) were purchased from Sigma-Aldrich. The resistivity of deionized water (DI) was 18.2MΩ·cm -1 , obtained using a Barnstead E-pure water system, was used for washing samples and preparing electrodes and electrolytes. All chemical reagents were used directly without additional purification.

[0041] 2.2.Ru 0.9-x Sn x Ni 0.1 Synthesis of O2

[0042] In Sn 0.9-x Ru 0.1 Ni 0.1During the synthesis of O2 (x = 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8), 0.175 g SnCl4·5H2O, 0.104 g RuCl3 and 0.0237 g NiCl2 were dissolved in 10 ml ethanol, and 0.5 ml HCl was added, and a uniform solution was formed by ultrasonic treatment for 1 hour. Next, the mixed uniform solution was transferred to a water bath and kept at 60°C for 12 hours until a solid solution was formed. The solid solution was then completely dried in an oven at 60°C. Finally, the dried precursor was annealed in a tube furnace at 450°C in air for 2 hours, the black product was collected, and washed three times with water and once with ethanol to remove impurities. Reference electrode Ru 0.4 Sn 0.6 The synthesis of O2 catalyst followed the same procedure.

[0043] 2.3. Material characterization:

[0044] The crystal structure was determined by Bruker D8 Advance ECO X-ray diffractometer (Cu, Kα, 40 kV, 25 mA) in the range of 10° to 80°. The system was equipped with a D\teX Ultra 1D silicon strip detector configured in X-ray fluorescence suppression mode. The powder samples were deposited on a zero-diffraction silicon sample stage. In addition, transmission electron microscopy (TEM), energy dispersive spectroscopy (EDS), high-resolution transmission electron microscopy (HR-TEM), and elemental distribution maps were recorded using a JEOL 2100 Cryo transmission electron microscope (TEM) equipped with a LaB6 emitter, operating at a voltage of 200 kV. To prepare the TEM samples, the electrocatalysts were sonicated in ethanol for 30 min to form a homogeneous dispersion, and then a drop of this dispersion was dropped on a TEM grid. SEM images were obtained using a Hitachi S4800 scanning electron microscope (SEM) at an accelerating voltage of 15 kV. SEM samples were prepared by fixing the powder samples on a SEM sample holder with carbon tape. X-ray photoelectron spectroscopy (XPS) was tested using a Thermo Fisher ESCALAB 250XI system.

[0045] 2.4. Electrocatalytic performance study

[0046] 2.4.1 Preparation of catalyst ink

[0047] In order to prepare a uniform ink, 5 mg Sn 0.9-x Ru 0.1 Ni 0.1O2 (x = 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8) was dispersed in a mixture of 1 ml of isopropyl alcohol (IPA, 0.48 ml), deionized water (0.48 ml) and 0.04 ml of Nafion solution (5 wt%), and then ultrasonicated for 1 hour. 0.4 Sn 0.6 The preparation of O2 catalyst ink adopted the same procedure.

[0048] 2.4.2 Preparation of electrodes

[0049] Electrochemical measurements OER activity and stability tests were performed using an electrochemical workstation (model CHI760D, CH Instruments) and a standard three-electrode electrochemical cell. The catalytic activity of the samples was recorded in 0.5M H2SO4 solution, using the prepared samples, platinum sheets and Ag / AgCl as working electrodes, counter electrodes and reference electrodes. In order to evaluate the OER activity of the catalyst, linear sweep voltammetry (LSV) tests were performed with a test voltage range of 0.2 to 1.2V and a scan rate of 10mV s-1. In the LSV test, the rotation speed of the rotating disk electrode (RDE) was 1600rpm. Electrochemical impedance spectroscopy (EIS) measurements were performed at different applied voltages with a frequency range of 100kHz to 0.5Hz and an amplitude of 10mV. The OER stability of the catalyst in acidic electrolyte was evaluated by constant current measurement (CP) and cyclic voltammetry (CV) tests. Figure 4 Represents the electrode preparation process.

[0050] 2. Physical Characterization

[0051] X-ray diffraction analysis

[0052] Figure 2 The XRD patterns of the samples are shown. Figure 1 ) shows RuxSn 1-x Ni 0.1 The diffraction peaks of O2 correspond to those of ilmenite-type RuO2 (JCPDS 71-2273), among which a significant (110) peak is observed at 28.1°, indicating that the incorporation of Sn and Ni does not change the lattice structure of ilmenite-type RuO2.

[0053] Scanning electron microscopy (SEM)

[0054] The surface morphology and microstructure of all samples were examined using a Nova-Nano SEM 450 scanning electron microscope. Figure 3 (a) shows Sn 0.4-x Ru 0.5 Ni 0.1SEM image of O2 (best sample). Figure 3 As shown, Sn 0.4-x Ru 0.5 Ni 0.1 The ultrafine nanoparticles of O2 are uniform in size. The distribution of Sn and Ni throughout the RuO2 is uniform. The elemental composition of the synthesized nanocomposite-based nanomaterials is Figure 3 The qualitative composition analysis revealed the presence of Sn, Ru, Ni, and oxygen elements. This elemental information provides valuable data on the composition and purity of the synthesized nanomaterials.

[0055] Electrochemical measurements

[0056] All prepared samples were first coated on a carbon electrode, and their OER performance was studied using a three-electrode system in 0.5 M H2SO4, with a platinum electrode and an Ag / AgCl electrode as the counter electrode and reference electrode, respectively. The study found that the best sample was Sn 0.5 Ru 0.4 Ni 0.1 O2, its OER activity reached 252.3mV, and the OER performance of the catalyst was comparable to that of the homemade Sn without Ni addition. 0.4 Ru 0.502 The incorporation of Ni increases the OER activity from 302 mV to 252.3 mV.

[0057] Figure 5 It's Sn 0.9-x Ru x Ni 0.1 O2 and Sn 0.5 Ru 0.4 Electrocatalytic OER performance of O2 in 0.5M H2SO4 electrolyte. Figure 5 The oxygen evolution reaction (OER) performance of different SnxRuyNizO2 compositions is shown by plotting the current density (mA / cm 2 ) and potential (V vs RHE). Sn 0.4 Ru 0.5 Ni 0.1 O2 (red curve) performed best, showing the highest current density at a lower potential, indicating that it requires less energy to drive the OER process and is the most efficient catalyst. In contrast, the reference catalyst Sn 0.4 Ru 0.6 O2 (blue curve) shows significantly lower activity, indicating the positive effect of Ni doping on performance. Other compositions containing different amounts of Ru and Ni also show improved performance compared to the undoped reference catalyst, but none reaches the performance of Sn 0.4 Ru 0.5 Ni0.1 The results show that the optimal balance between Ru and Ni content leads to enhanced catalytic activity, which demonstrates the role of Ni in improving OER performance in these mixed oxide catalysts.

[0058] Figure 6 It's Sn 0.4 Ru 0.5 Ni 0.1 O2 and Sn 0.4 Ru 0.6 The Tafel slope of O2 is shown in the figure. The Tafel slope of the two catalysts is Sn 0.4 Ru 0.5 Ni 0.1 O2 (red line) and Sn 0.4 Ru 0.6 O2 (blue line), by plotting the overpotential (V vs RHE) versus the logarithm of the current density (Log(j)). The Tafel slope is an important parameter for characterizing the kinetics of the oxygen evolution reaction (OER). A lower Tafel slope means faster reaction kinetics, meaning that the reaction requires less overpotential to achieve a certain increase in current density. 0.4 Ru 0.6 The Tafel slope of O2 (blue line) is 86.3 mV / dec, which is lower than that of Sn. 0.4 Ru 0.5 Ni 0.1 O2 (red line) is 123.5 mV / dec, which indicates that the undoped Sn 0.4 Ru 0.6 O2 has faster OER kinetics than the nickel-doped samples, although the nickel-doped catalyst has better overall current density at lower overpotentials. The higher Tafel slope of the nickel-doped samples indicates that although doping improves catalytic activity, the reaction mechanism becomes slightly more complicated, probably due to the interaction between nickel and ruthenium in the catalytic process.

[0059] Figure 7 It's Sn 0.4 Ru 0.5 Ni 0.1 Stability diagram of O2. The diagram shows that the catalyst Sn 0.4 Ru 0.5 Ni 0.1 O2 exhibits good stability, and after a rapid initial potential drop, it exhibits long-term stable performance for more than 1200 min, indicating its persistent oxygen evolution reaction (OER) activity.

[0060] The above description is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Any modifications, equivalent substitutions and improvements made by any technician familiar with the technical field within the technical scope disclosed by the present invention and within the spirit and principle of the present invention should be covered by the protection scope of the present invention.

Claims

1. A method for synthesizing a low-cost acidic cut-off oxygen evolution catalyst, characterized in that: The following steps are involved: (1) Dissolving SnCl4·5H2O, RuCl3 and NiCl2 in ethanol to prepare a mixed solution; (2) adding HCl to the mixed solution obtained in step (1) and forming a homogeneous solution by ultrasonic treatment; (3) transferring the homogeneous solution obtained in step (2) into a water bath and maintaining the reaction at a certain temperature for several hours until a solid solution is formed; (4) completely drying the solid solution obtained in step (3) in an oven to obtain a precursor; (5) annealing the precursor obtained in step (4) in air in a tube furnace and collecting a black product; (6) Washing the black product collected in step (5) with water, and then washing with ethanol to remove impurities, thereby obtaining a low-cost acidic cut-off oxygen evolution catalyst.

2. The method for synthesizing a low-cost acidic cut-off oxygen evolution catalyst according to claim 1, characterized in that: The SnCl4·5H2O described in step (1) is 0.175 g, the RuCl3 is 0.104 g, and the NiCl2 is 0.0237 g.

3. The method for synthesizing a low-cost acidic cut-off oxygen evolution catalyst according to claim 1, characterized in that: The amount of ethanol in step (1) is 10 ml.

4. The method for synthesizing a low-cost acidic cut-off oxygen evolution catalyst according to claim 1, characterized in that: In step (2), the amount of HCl is 0.5 ml.

5. The method for synthesizing a low-cost acidic cut-off oxygen evolution catalyst according to claim 1, characterized in that: The ultrasonic treatment time in step (2) is 1 hour.

6. The method for synthesizing a low-cost acidic cut-off oxygen evolution catalyst according to claim 1, characterized in that: In step (3), the reaction is maintained at 60° C. for 12 hours until a solid solution is formed.

7. The method for synthesizing a low-cost acidic cut-off oxygen evolution catalyst according to claim 1, characterized in that: The temperature of the oven in step (4) is 60°C.

8. The method for synthesizing a low-cost acidic cut-off oxygen evolution catalyst according to claim 1, characterized in that: Annealing conditions in step (5): annealing at 450°C for 2 hours.

9. The method for synthesizing a low-cost acidic cut-off oxygen evolution catalyst according to claim 1, characterized in that: In step (6), the black product is washed three times with water and then washed once with ethanol to remove impurities, thereby obtaining a low-cost acidic cut-off oxygen evolution catalyst.

10. A low-cost acidic cut-off oxygen evolution catalyst synthesized according to the method according to any one of claims 1 to 9.